2010
DOI: 10.1088/0031-9155/55/24/007
|View full text |Cite
|
Sign up to set email alerts
|

A constrained reconstruction technique of hyperelasticity parameters for breast cancer assessment

Abstract: In breast elastography, breast tissue usually undergoes large compression resulting in significant geometric and structural changes. This implies that breast elastography is associated with tissue nonlinear behavior. In this study, an elastography technique is presented and an inverse problem formulation is proposed to reconstruct parameters characterizing tissue hyperelasticity. Such parameters can potentially be used for tumor classification. This technique can also have other important clinical applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 35 publications
(36 reference statements)
1
29
0
Order By: Relevance
“…45 as well as in this study (not shown). In addition, these choices were consistent with the E values of normal breast tissues and those of breast tumors reported in the literature, which were 3-33 kPa and 6-107 kPa, respectively [35][36][37][62][63][64] as shown in Table SI in the supplementary material. The diameters of model tumors were 11.5 ± 0.3 mm, 10.3 ± 0.3 mm, 7.8 ± 0.2 mm, and 6.2 ± 0.2 mm, respectively.…”
Section: Breast Models and The Measurement Proceduressupporting
confidence: 89%
“…45 as well as in this study (not shown). In addition, these choices were consistent with the E values of normal breast tissues and those of breast tumors reported in the literature, which were 3-33 kPa and 6-107 kPa, respectively [35][36][37][62][63][64] as shown in Table SI in the supplementary material. The diameters of model tumors were 11.5 ± 0.3 mm, 10.3 ± 0.3 mm, 7.8 ± 0.2 mm, and 6.2 ± 0.2 mm, respectively.…”
Section: Breast Models and The Measurement Proceduressupporting
confidence: 89%
“…Since the 2000s, this focus has shifted to parameters that express the nonlinear material behavior of biological tissues, such as nonlinear elasticity, hyperelasticity and viscoelasticity. Some researchers [6], including Hall et al [7] and Mehrabian et al [8,9], have applied ultrasound and finite element inverse analysis to determine the elastic nonlinearity under large strains (around 10 % axial strain). Additionally, many researchers have reported dynamic multifrequency elastography for viscoelastic imaging using MRI and external oscillation devices [10][11][12].…”
Section: Noninvasive Breast Cancer Diagnosismentioning
confidence: 99%
“…By separating these scales, they reported a local and precise reconstruction. For other interesting aspects of the problem, see also [1,4,7,11,23,27,32]. All the above works, deal with the static approach.…”
Section: Literature Reviewmentioning
confidence: 99%
“…is a sequence of solutions to the discrete optimization problem (32). Then every subsequence of * h has a convergent subsequence with limit point as a solution to the minimization problem (30).…”
Section: Application To the Elasticity Imaging Inverse Problemmentioning
confidence: 99%